Metales traza en el pepino de mar Hololhuria (Halodeima) mexicana del Caribe de Costa Rica - Rojas, María Teresa; Acuña, Jenaro A.; Rodríguez, Olga M. (Revista de Biología Tropical, 1998)
The concentrations and in-tissue distributions of six metals, were determined in sea-cucumbers Holofhuria (Halodeima) mexicana Ludwig 1875 from the Costa Rican Caribbean sea, by the atomle absorption technique. The samples were taken over a period of 16 months between October 1987 and December 1989, with sizes ranging between 17 and 25 cm long and weights from 280 to 600 g. The metal concentration ranges (mg kg", dry weight), were Cd 0.1-2.5; Pb 0.2-26; Mn 4.1-46; Cu 1.3-69; Zn 14-174; Fe 20-1044. and Ihe respiratory tree was the structure that showed in general the higher levels of metals, except for Cu and Pb which were higher in the muscles and the body wall, respectively. This paper constitutes an important data base for future comparisons dealing with activities involving coastal impact since there is no previous information about trace metal content in similar species from this region of the Caribbean.